Identification and characterization of ACR gene family in maize for salt stress tolerance - Fang, Hui; Shan, Tingyu; Gu, Haijing; Chen, Junyu; Qi, Yingxiao; Li, Yexiong; Saeed, Muhammad; Yuan, Jinchao; Li, Ping; Wang, Baohua (Frontiers in Plant Science, 2024)
Members of the ACR gene family are commonly involved in various physiological processes, including amino acid metabolism and stress responses. In recent decades, significant progress has been made in the study of ACR genes in plants. However, little is known about their characteristics and function in maize. Here, we present the characteristics and functional properties of maize ACR genes. A total of 28 ZmACR genes were identified, and their molecular characteristics were extensively described. Two gene pairs arising from segmented replication events were detected in maize, and 18 collinear gene pairs were detected between maize and 3 other species. Through phylogenetic analysis, three subgroups were revealed, demonstrating distinct divergence between monocotyledonous and dicotyledonous plants. Analysis of ZmACR cis-acting elements revealed the optional involvement of ZmACR genes in light response, hormone response and stress resistance. Expression analysis of 8 ZmACR genes under salt treatment clearly revealed their role in the response to salt stress. Ectopic overexpression of ZmACR5 in Arabidopsis notably reduced salt tolerance compared to that of the wild type under salt treatment, suggesting that ZmACR5 has a negative role in the response to salt stress. Taken together, these findings confirmed the involvement of ZmACR genes in regulating salt stress and contributed significantly to our understanding of the molecular function of ACR genes in maize, facilitating further research in this field.